PENGARUH PEMBELAJARAN DI LUAR KELAS TERHADAP MINAT DAN KETERTARIKAN SERTA PRESTASI BELAJAR PESERTA DIDIK PADA MATA PELAJARAN IPS KELAS VIII SMP NEGERI 11 BANJARBARU - syahidan Arifin (Universitas Lambung Mangkurat, 2015)
The purpose of this study was to analyze the effect of learning outside the classroom to enthusiasm, interest, and learning achievement of students in social studies learning. This research uses experimental research design. Forms of experimentation design used is True Experimental with Posttest Only Control Design. While Posttest Only Control Design, the design of this research, there are two groups, each of which are chosen randomly. The first group was given treatment and the other group did not. Called the group treated experimental group and the untreated group called the control group. The study was conducted at SMP Negeri 11 Banjarbaru. The research sample of students of class VIII Academic Year 2015/2016 totaling 230 class A to class VIII VIII F. From the results it can be concluded that there are significant learning outside the classroom to enthusiasm, interest, and student achievement. With this method of learning outside the classroom involving students showed perseverance, passion, enthusiasm, as well as full participation among fellow students and teachers. Their interest in students with learning IPS can give rise to interest in learning. If the interest and appeal to a lesson has emerged on students is in itself a lesson it will feel easy and fun so that student learning outcomes increases. With good interest and attraction the achievement belajarpun be good.Keywords: IPS, interests, learning outside classroom, academic achievement